2020
DOI: 10.2196/18358
|View full text |Cite
|
Sign up to set email alerts
|

Teaching the National Institutes of Health Stroke Scale to Paramedics (E-Learning vs Video): Randomized Controlled Trial

Abstract: Background Prompt and accurate identification of stroke victims is essential to reduce time from symptom onset to adequate treatment and to improve neurological outcomes. Most neurologists evaluate the extent of neurological deficit according to the National Institutes of Health Stroke Scale (NIHSS), but the use of this scale by paramedics, the first healthcare providers to usually take care of stroke victims, has proven unreliable. This might be, at least in part, due to the teaching method. The v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 30 publications
2
38
0
Order By: Relevance
“…This version of the module contains video extracts in all chapters, including for the items related to dysarthria, level of consciousness – global, and level of consciousness – questions. In the previously studied version of our module (version 20), there were no video extracts for these items [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This version of the module contains video extracts in all chapters, including for the items related to dysarthria, level of consciousness – global, and level of consciousness – questions. In the previously studied version of our module (version 20), there were no video extracts for these items [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Since the release of Patrick Lyden’s didactic video in 1994 [ 22 ], the development of NIHSS teaching material has been rather limited. We have recently shown that compared to this didactic video, a highly interactive e-learning module improved NIHSS knowledge acquisition in paramedics [ 23 ]. We defined this module as “highly interactive” because it uses multiple learning mechanics to promote interaction and engagement.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, most participants were unable, regardless of their assigned intervention, to reconstruct either the donning (assessed preintervention) or the doffing (assessed postintervention) sequences. This potential limitation has already been highlighted in the paper describing the development of the gamified e-learning module used in this study [ 13 ], though cut scenes were embedded to provide direct demonstration [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This interactive module was created under Articulate Storyline 3 (Articulate Global, New York, USA). Feedback [ 19 ], pretesting [ 16 ], avoiding content skipping [ 20 , 21 ], embedded videos [ 22 ] and gamification [ 23 ] were used as learning mechanics. Gamification was used for donning and doffing sequences.…”
Section: Methodsmentioning
confidence: 99%